Exploring Secondary School Biology Teachers’ Competency in Practical Work - Fadzil, H. M.; Saat, R. M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
A competent biology educator should be efficient in the design, organizing, and execution of practical work and the evaluation of practical skills. Nevertheless, according to past research, the participation of students in conducting experiments is inadequate, and the teachers are not guiding them effectively. One of the issues that could lead to this problem is the lack of efficiency of the teacher to carry out practical work. To gauge this problem, a qualitative study has been conducted. The study involves eight biology teachers from eight secondary schools in two states in Malaysia, namely Kuala Lumpur and Selangor. Data were collected through observation at biology laboratory, interviews with biology teachers, and analysis of related documents such as lesson plans. Collected data were analyzed using constant comparative data analysis methods to explain the core phenomenon of this study. Three (3) themes emerged in this study: (i) difficulty in designing and planning practical lessons effectively, (ii) insufficient preparation before conducting practical lessons and (iii) improper evaluation of students’ achievement in biology practical lessons. The results of this study offer information on the competence of biology teachers, which can be used to enhance the quality and standards of biology teaching and learning.